Intrauterine death from placental abruption: influence of labor duration and mode of delivery on maternal outcomes - Van Hees, Louis; Danger, Robin; Turbelin, Caroline (Frontiers in Medicine, 2025)
IntroductionIntrauterine fetal death (IUFD) caused by retroplacental hematoma (RPH) can lead to serious maternal complications including coagulopathies and hemorrhage. A prolonged diagnostic-to-expulsion delay may increase coagulation risks. Vaginal delivery (VD) prolongs this delay, while cesarean delivery poses higher hemorrhagic risks. This study aimed to assess the relationship between expulsion delay and complications, identify a time threshold for increased risks, and evaluate VD feasibility.Material and methodsWe conducted a retrospective single-center study at the University Hospital of Martinique, including all patients presenting with RPH and IUFD between January 2003 and December 2022. Complications were defined by a composite criterion, including the need for blood transfusion, severe anemia or admission to an intensive care unit.ResultsVD was attempted in 26 of the 27 patients included and successfully achieved in 85% of the cases. All cesarean deliveries resulted in complications (p = 0.12), with 50% experiencing severe hemorrhage, compared to 21.7% of VD cases (p = 0.23). No statistically significant association was found between the expulsion delay and the occurrence of complications (p = 0.20). A low fibrinogen level upon admission was associated with an increased risk of severe hemorrhage (p = 0.01) and complications (p = 0.01).ConclusionIn this study, no evidence was found to suggest an association between the diagnostic-to-expulsion interval and maternal complications. Low fibrinogen levels at admission appear to be a prognostic factor for severe hemorrhage and could have therapeutic implications. Vaginal delivery remains feasible even in the presence of coagulopathies at admission.